Trauma Attending Physician Continuity: Does it Make a Difference? - Jacobs, David G.; Sarafin, Jennifer L.; Head, Karen E.; Christmas, A Britt; Huynh, Toan; Miles, William S.; Sing, Ronald F. (The American surgeon, 2010)
Continuity of care is important in achieving optimal outcomes in trauma patients, but the optimal length of the trauma attending (TA) rotation is unknown. We hypothesize that longer TA rotations provide greater continuity, and therefore improve outcomes. We did a retrospective comparison of trauma patient outcomes from two consecutive 6-month periods during which we transitioned from a 1-month TA rotation to a 1-week TA rotation. The Wilcoxon rank sum test, and the χ 2 were used for statistical analysis. Over the 12-month study period 1924 patients were admitted to the Trauma Service. The two groups were similar with regard to age, gender, injury mechanism, Injury Severity Score and Glasgow Coma Scale scores, and Abbreviated Injury Scores for the chest, abdomen, and extremities. Although mortality, patient charges, and violations of the standard of care were similar between the two groups, overall morbidity was lower (18.6% vs 23.2%), and hospital length of stay higher (9.07 days vs 8.41 days) in the 1-week TA group compared with the 1-month TA group. A one-week TA rotation was associated with a longer hospital length of stay, but improved morbidity. Longer TA rotations do not necessarily provide improved continuity or improved outcomes.